Pelatihan Optimasi Google Search Engine dan Google Lens Untuk Media Pembelajaran Siswa SMK Negeri 18 Samarinda - Nirawana, I Wayan Sugianta; Subastian, Eko; Suwandi, Bayu Pratama; Kevin Fernandy Turang; Wahyudi Mas’ud (Jurnal Pengabdian Kampus, 2024)
The era of advanced technology in the world of education, demands adaptation from educators to use technology for learning. Merdeka curriculum also provides learning opportunities not only in class, but also outside the classroom. The smartphone devices used need to be optimized for learning, therefore educators must improve their skills and mastery of the use of technology. SMK Negeri 18 Samarinda already has a laboratory, but the facilities are not adequate, besides that some teacher and student have never used google lens. For the google search engine teacher and student are familiar, but there are several keyword optimization operators that are not yet known. The purpose of the service is to provide training in optimizing google search engine and google lens as a learning media for teachers and students. There are 3 methods used for this training. First, the lecture method in explaining the material. Second, the demonstration method for how to use it. Third, the practice method together with teacher and students practicing the use of google search engine and google lens optimization. The result achieved in this training as a whole from 32 participants who filled in where very satisfied with this training, namely 46,9% and satisfied by 34,4%. The training material also relevant to learning needs with very relevant 46,9% and relevant 34,4%. News skills are also obtained from both the google search engine features and google lens as supporting learning media. Teacher and students are also motivated by the training and can apply it well. This training program is expected to be applied ini classroom learning and outside the classroom using google lens.